2020
DOI: 10.3390/ani10081278
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Lung Inflammation and Aerobic Threshold in Standardbred Racehorses with Mild-Moderate Equine Asthma

Abstract: Mild–moderate equine asthma (MEA) is a common disease of young racehorses characterized by inflammation of the lower airways diagnosed by cytological examination of bronchoalveolar lavage fluid (BALF), and it is considered an important cause of poor performance. The most common parameter of athletic capacity associated with horse performance is the speed at 4 mmol/L of lactate (VLA4). The aim of the present work was to evaluate the relation between the different BALF inflammatory cells and VLA4 in racehorses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…To perform the cytological examination, a few drops of pooled BALf were cytocentrifugated (ROTOFIX 32, Hettich Cyto-System, Germany) at 26× g for 5 min. The slides were air dried, stained with May-Grünwald Giemsa and Perl's Prussian blue and observed under a light microscope at 400× and 1000× for 400-cell leukocyte differential count [31]. To perform the TW, a 60 mL pre-warmed sterile saline 0.9% was flushed into the intrathoracic portion of the tracheal lumen, re-aspirated and transferred into sterile plain tubes for microbiological evaluation [29].…”
Section: Airway Endoscopy Bal and Twmentioning
confidence: 99%
“…To perform the cytological examination, a few drops of pooled BALf were cytocentrifugated (ROTOFIX 32, Hettich Cyto-System, Germany) at 26× g for 5 min. The slides were air dried, stained with May-Grünwald Giemsa and Perl's Prussian blue and observed under a light microscope at 400× and 1000× for 400-cell leukocyte differential count [31]. To perform the TW, a 60 mL pre-warmed sterile saline 0.9% was flushed into the intrathoracic portion of the tracheal lumen, re-aspirated and transferred into sterile plain tubes for microbiological evaluation [29].…”
Section: Airway Endoscopy Bal and Twmentioning
confidence: 99%
“…For example, in a review, the plant-based diets (which usually reduce the in ammation) had no effect on physical performance compared to meats (which increase the DII score) (33). However, an animal study showed that in ammation in the body reduces physical function by increasing the number of neutrophils in the pulmonary ducts and impairing alveolar gas exchange (34). In ammation has also been shown to cause cytokine cascades that are related to fatigue, which can affect athletic performance (35).…”
Section: Discussionmentioning
confidence: 99%
“…The treadmill test was performed with a slope of 3°. The standardized protocol consisted of a warm-up period of 4 min at a walk (1.5 m/s) and 3 min at a trot (6 m/s), and then the treadmill speed was increased by 1 m/s every minute from 7 m/s until the horse became unable to maintain the belt speed [ 21 , 22 ]. At this time, the belt speed was rapidly decreased to 1.5 m/s.…”
Section: Methodsmentioning
confidence: 99%
“…After that, samples were immediately transferred into tubes with potassium fluoride. In order to obtain the lactate curve, samples were taken at rest, at the end of the warm-up period at a trot, at the end of each incremental step, and during the recovery period at 1, 5, 15, and 30 min after the end of the exercise [ 21 ]. Lactate concentration was determined on plasma samples.…”
Section: Methodsmentioning
confidence: 99%